Labour problems of a developing economy - Aziz,Abdul (New Delhi, 1984)
This book, which contains eight Chapers highlights some aspects of Indian labour such as the role of trade unions in promoting economic deve lopment, the need for, and the stra tegy to be followed to, organise agricultural labourers, workers' views on participative management, trends in collective bargaining, the relevance of Gandhian approach to industrial relations and the policy regarding, and equity in, labour remuneration. While attempting to bring out the basic issues involved, the papers also endeavour to evaluate the policy of the State regarding bonus, level and structure of wages and so on. Some interesting suggestions are also made on the issues of equity in wages, bonus and the question of unionising agricul tural labourers.